Perceived partial social integration, levels of distress and resilience, and COVID-19 vaccine rejection of Jewish and Arab citizens of Israel - Eshel, Yohanan; Kimhi, Shaul; Marciano, Hadas; Adini, Bruria (Frontiers in Public Health, 2022)
The present study examines the role of perceived partial social integration (PPSI) in determining the rejection of the COVID-19 vaccine of Jewish and Arab citizens of Israel. We assumed that higher levels of PPSI will be associated with higher levels of vaccine rejection in both groups. We further assumed that the Arab minority group will regard itself as less socially integrated into the Israeli society and will therefore reject the COVID-19 vaccine to a greater extent than the majority group. We conjectured that the Arab respondents will express a higher level of psychological distress and a lower level of resilience compared with the Jewish participants. Furthermore, we conjectured that the perceived partial social integration (PPSI) score will significantly predict the levels of distress and resilience of the Jewish but not the Arab sample. This group difference was explained by the partial denial that characterizes the Arab respondents. The results supported our hypotheses. The research hypotheses are examined using a relatively large sample of the Israeli public, including 208 Arab and 600 Jewish adults, who have responded to an anonymous questionnaire pertaining, among other issues, to partial social integration and the individual level of vaccine uptake.